Alterations in plasma cytokine levels in chinese children with autism spectrum disorder. Issue 7 (9th March 2018) - Hu, Chun‐Chun; Xu, Xiu; Xiong, Guo‐Liang; Xu, Qiong; Zhou, Bing‐Rui; Li, Chun‐Yang; Qin, Qi; Liu, Chun‐Xue; Li, Hui‐Ping; Sun, Yun‐Jun; Yu, Xiang
Abstract : Genetic alterations, together with environmental risk factors during infancy and childhood, contribute significantly to the etiology of autism spectrum disorder (ASD), a heterogeneous neurodevelopmental condition characterized by impairments in social interaction and restricted, repetitive behaviors. Mounting evidence points to a critical contribution of immunological risk factors to the development of ASD. By affecting multiple neurodevelopmental processes, immune system dysfunction could act as a point of convergence between genetics and environmental factors in ASD. Previous studies have shown altered cytokine levels in individuals with ASD, but research in Asian populations are limited. Here, we measured the plasma levels of 11 candidate cytokines in ASD and typically developing (TD) children. The cohort included 41 TD children and 87 children with ASD, aged 1–6 years. We found that as compared to the TD group, children with ASD had higher plasma levels of Eotaxin, TGF‐β1 and TNF‐α. The increase in TGF‐β1 level was most significant in males, while the increase in Eotaxin was most significant in females. Eotaxin level negatively correlated with the social affect score (SA) in ADOS, while TNF‐α level positively correlated with total development quotient (DQ), measured using GMDS. These pilot findings suggest potentially important roles of Eotaxin, TGF‐β1 and TNF‐α in ASD in the Chinese population. Autism Res 2018, 11: 989–999 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Alteration of immune system function is an important risk factor for autism spectrum disorder (ASD). Here we found that the levels of cytokines, including Eotaxin, TGF‐β1 and TNF‐α, are elevated in Chinese children with ASD, as compared to typically developing children. The change in TGF‐β1 level was most prominent in boys, while that of Eotaxin was more significant in girls. These results provide evidence for changes in cytokine profile in Chinese children with ASD.